Effects of Biochar and Sepiolite on Pb and Cd Dynamics in Contaminated Soil with Different Corn Varieties - Peiyi Zeng; Muqing Yang; Shujuan He; Ying Kong; Xian Zhu; Zitao Ma; Min Wu (Toxics)
Biochar can stabilize heavy metals in soil and inhibit their accumulation in plants as a soil amendment. Sepiolite has also shown good effects in the remediation of soil heavy metal pollution. In this study, biochar, sepiolite, and biochar–sepiolite combined amendments were used to evaluate the accumulation of cadmium (Cd) and lead (Pb) in soil by 29 corn varieties. The concentrations of Cd and Pb in corn fruits were the lowest (Pb: 0.11 mg/kg, Cd: 0.06 mg/kg). There was a significant difference (p < 0.05) in Pb and Cd accumulation in the roots, stems, leaves, and fruits in the 29 corn varieties. The BCF and TF values of Pb and Cd in the 29 corn varieties were different, and Pb is more likely to accumulate in the roots, Cd is more likely to accumulate in the leaves, and neither heavy metal is easily translocated to the corn fruits. The combination of biochar and sepiolite creates an environment conducive to the retention of heavy metals in the root zone, effectively reducing the risk of heavy metal contamination in the edible parts of the plants. After considering various factors, such as environmental adaptability, we recommend using sepiolite and biochar combined as a soil amendment material and planting the WG1790 variety. Field experiments are needed to verify the effects. These results provide scientific evidence and new strategies for the selection of corn varieties and soil amendments.